Macrofauna and Nematode Abundance in the Abyssal and Hadal Zones of Interconnected Deep-Sea Ecosystems in the Kuril Basin (Sea of Okhotsk) and the Kuril-Kamchatka Trench (Pacific Ocean) - Kamenev, Gennady M.; Mordukhovich, Vladimir V.; Alalykina, Inna L.; Chernyshev, Alexei V.; Maiorova, Anastassya S. (Frontiers in Marine Science, 2022)
The Kuril Basin and the Kuril-Kamchatka Trench are two interconnected deep-sea ecosystems both located in one of the most highly productive regions of the world’s oceans. The main distinguishing features of these deep-sea ecosystems are the low oxygen concentration in the near-bottom water in the Kuril Basin, and the high hydrostatic pressure in the trench. We investigated the abundance of meio- and macrobenthic nematodes and macrofauna on the Kuril Basin floor (depths of 3,300–3,366 m) and in the Kuril-Kamchatka Trench area (depths of 3,432–9,539 m), as well as the influence of some environmental factors on the quantitative distribution of bottom fauna. This was not studied so far. The study also focused on the species composition and quantitative distribution of Polychaeta and Bivalvia, which were dominant in abundance among macrofaunal samples. The main factors influencing the quantitative distribution of macrofauna and nematodes were depth, oxygen concentration, and structure of bottom sediments. The Kuril Basin bottom communities are characterized by a high abundance of nematodes and macrofauna, a high species richness of polychaetes, and a pronounced dominance of small-sized species of Polychaeta and Bivalvia, which are probably more tolerant to low oxygen concentrations. Compared to the Kuril Basin, the Kuril-Kamchatka Trench area (at depths of 3,432–5,741 m) had a more diverse and abundant macrofauna, and a very high abundance of meio- and macrobenthic nematodes. In the trench (at depths more than 6,000 m), the diversity of macrofauna and the abundance of macrobenthic nematodes decreased, while the abundance of macrofauna increased with increasing depth. On the trench floor, the macrofaunal abundance was highest due to the high density of populations of several bivalve and polychaete species, apparently adapted to the high hydrostatic pressure on the trench floor. Obviously, the high primary production of surface waters supports the diverse and abundant deep-sea bottom fauna in the studied areas of the northwestern Pacific. Furthermore, a large number of animals with chemosynthetic endosymbiotic bacteria were found in the bottom communities of the Kuril Basin and the Kuril-Kamchatka Trench. This suggests a significant contribution of chemosynthetic organic carbon to functioning of these deep-sea ecosystems.